Use of high-performance graphics processing units for power system demand forecasting. - Ting He (Journal of electrical engineering & technology)
Load forecasting has always been essential to the operation and planning of power systems in deregulated electricity markets. Various methods have been proposed for load forecasting, and the neural network is one of the most widely accepted and used techniques. However, to obtain more accurate results, more information is needed as input variables resulting in huge computation costs in the learning process. In this paper, to reduce training time in multi-layer perceptron-based short-term load forecasting, a graphics processing unit (GPU)-based computing method is introdiced. The proposed approach is tested using the Korea electricity market historical demand data set. Results show that GPU-bases computing greatly reduces computational costs.